Functional conformations for pyruvate carboxylase during catalysis explored by cryoEM - Lasso, Gorka (2014)
The tetrameric enzyme Pyruvate Carboxylase (PC), a biotin-dependent carboxylase, produces oxaloacetate by two consecutive reactions that take place in distant active sites. Previous crystal structures revealed two different configurations for PC tetramers, the so-called symmetric and asymmetric, which were understood as characteristic molecular architectures for PC from different organisms. We have analyzed PC samples from Staphylococcus aureus while the enzyme generates oxaloacetate, expecting PC tetramers to display the conformational landscape relevant for its functioning. Using cryoEM and sorting techniques we detect previously defined symmetric and asymmetric architectures, demonstrating that PC maps both arrangements by large conformational changes. Furthermore, we observe that each configuration is coupled to one of the two consecutive enzymatic reactions. The findings describe the structural transitions relevant for the allosteric control of the multifunctional PC, and demonstrate that by cryoEM and classification we can characterize freely working macromolecules.